PENGARUH RASIO PROFITABILITAS TERHADAP HARGA SAHAM PADA PT SEMEN INDONESIA (PERSERO) TBK - Aris, Muhammad Saleh; Darwis; Damirah; Ismayanti (Scimadly Publishing, 2025)
This study investigates the effect of Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Earnings Per Share (EPS) on stock prices, both individually and collectively. Employing a quantitative approach, the research utilizes secondary data sourced from the financial statements of PT Semen Indonesia (Persero) Tbk. The analysis involves classical assumption testing, multiple linear regression, and both t-tests and F-tests conducted using SPSS software. The findings reveal that ROE has a positive and significant impact on stock prices, while NPM exhibits a significant but negative influence. In contrast, ROA and EPS show no meaningful effect when examined separately. However, when tested simultaneously, all four variables demonstrate a significant relationship with stock price fluctuations. This study acknowledges certain limitations, particularly regarding the scope of data, variables, and methodology. Future research is encouraged to incorporate external macroeconomic factors such as inflation, interest rates, and government policy to provide a more comprehensive analysis.